TRENDS AND POSSIBLE CAUSES OF MENTAL ILLNESS: THE CASE OF PSYCHIATRY WARD IN JIMMA UNIVERSITY SPECIALIZED HOSPITAL, ETHIOPIA - Berhanu Nigussie Worku; Solomon Shiferaw (European Scientific Journal, ESJ, 2014)
The main objective of this study was to investigate the trends and factors of mental illness of psychiatric patients in the psychiatry Ward of Jimma University Specialized Hospital.Purposive sampling technique was used to select the participants of the study. Accordingly, 636 patients' cards were analyzed. Moreover, 55 psychiatric patients, 56 care givers and 13 psychiatric ward staff were involved in the study. The instruments designed to obtain the data were observation check list, document analysis form, and semi-structured interview guide. The collected data were analyzed using both quantitative and qualitative techniques.The study was also ethically cleared by Institutional Ethical Review Board.The results of the study revealed that schizophrenia, major depression disorder, brief psychosis and anxiety disorder respectively were the frequent mental illnesses in the ward, by looking into the patients’ documents of 51/2 years. These disorders generally attacked the productive age group (20 to 30 years of age), the major reasons of which could be attributed to drug use (mostly ‘Khat’),stress caused by academic failure, joblessness, and lack of youth friendly recreation areas. In addition, the findingsshowed that the trends of the mental illnessesin the ward weregenerally increasing. The results also revealed that drug default, substance use, economic problem, family conflicts, loss of family members, poor social support, stigma and discrimination and repeated chronic illnesses were the major aggravating factors of mental illnesses in Jimma areas, in particular.The alarmingly increasing number of psychiatric patients, due to varies factors, needs serious attention. In addition to aggressively working on awareness creation, early identification and intervention of the disorder need to be targeted. Quality services should also be provided to patients who are visiting the ward.